As representações discursivas da reforma do ensino médio, lei 13.415/2017, em diferentes gêneros do discurso - Galvão, Flávia Motta de Paula (2019)
This thesis is the result of a research that aimed at investigating the discursive representations of the “Reforma do Ensino Médio” (Brazilian High School Reform), “Lei” (Law) n. 13.415/2017, constructed in three different genres: governmental advertisements, online reports, and virtual comments. Our theoretical basis are: Critical Discourse Analysis (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 1989, 2001, 2003, 2006, 2009), the studies on globalization, languages and technologies (FAIRCLOUGH, 2006; GIDDENS, 2003; CASTELLS, 2000; RECUERO, 2009; POSTER, 2000) and researches about the history of education and curricular changes (CAMPELLO, 2009; CUNHA, 1973; DOMINGUES, 2000; KUENZER, 1994, 1997, 2000; SAVIANI, 1987, 2007). As methodology, we adopted the qualitative research (BAUER; GASKELL, 2002) and the Critical Discourse Analysis. The corpus is constituted by: a) three governmental advertisements, broadcasted between 2016 and 2017, approval years of both the “Medida Provisória” (Provisional Measure) n. 076 and the Law n. 13.415; b) three online reports, from three different websites – Globo.com (G1), Nova Escola, and UOL – all broadcasted on February 16th, 2017, day when the law was sanctioned; c) 21 virtual comments available at the same websites as the reports. For the data analysis, we used categories from the Critical Discourse Analysis, namely: vocabulary, intertextuality, interdiscursivity, evaluation and modality. The analysis demonstrated that the most recurrent discourses in the governmental advertisements and in the online reports converge to a discursive representation favorable to the Reform, which contributes to an evaluation of the Reform as a necessary measure. Besides, in these two genres, the intertextuality occurs, majorly, marked by the Federal Government voice, mainly by the sayings of Michel Temer and former minister of education, Mendonça Filho. On the other hand, most of the virtual comments construct a discursive representation contrary to the “Reforma do Ensino Médio”. These discourses question, mainly, the undemocratic process of the approval of the Law and its legitimacy, as well as the “new” curriculum. Thus, the analytical chapter of this thesis enables reflections about the discursive representations of the Reform, showing that there are discourses favorable to the changes in the curriculum and others that denies the validity and necessity of these changes. In this sense, we notice that certain linguistic-discursive representations collaborate to the maintenance of asymmetrical relations of power, once the governmental discourse is prevailing to the others, beside demonstrating that the actions and decisions by the government do not depend necessarily on the people’s will, which are legitimated, many times, by the media in different means of communication.